Looking downstream: the role of cyclic AMP-regulated genes in axonal regeneration - Siddiq, Mustafa M.; Hannila, Sari S. (Frontiers in Molecular Neuroscience, 2015)
Elevation of intracellular cyclic AMP (cAMP) levels has proven to be one of the most effective means of overcoming inhibition of axonal regeneration by myelin-associated inhibitors such as myelin-associated glycoprotein, Nogo, and oligodendrocyte myelin glycoprotein. Pharmacological manipulation of cAMP through the administration of dibutyryl cAMP or rolipram leads to enhanced axonal growth both in vivo and in vitro, and importantly, upregulation of cAMP within dorsal root ganglion neurons is responsible for the conditioning lesion effect, which indicates that cAMP plays a significant role in the endogenous mechanisms that promote axonal regeneration. The effects of cAMP are transcription-dependent and are mediated through the activation of protein kinase A and the transcription factor CREB. This leads to the induction of a variety of genes, several of which have been shown to overcome myelin-mediated inhibition in their own right. In this review, we will highlight the pro-regenerative effects of arginase I, interleukin-6, secretory leukocyte protease inhibitor, and metallothionein-I/II, and discuss their potential for therapeutic use in spinal cord injury.